CORRELATION OF THE HEADROOM SUPERVISION AND THE ELECTRONIC NURSING DOCUMENTATION METHOD IN THE ERA OF COVID-19 - Putri, Dila Sari; Febriani, Nelly (Universitas Islam Negeri Alauddin Makassar, 2021)
The application of electronic nursing documentation makes it difficult for nurses to adapt to the system. Supervision carried out by the head of the room can affect the quality of electronic nursing documentation. The purpose of this study was to identify the correlation between the supervision of the head of the room and the implementation of nursing care using the Electronic Nursing Documentation. This study uses a descriptive correlation research design using a cross sectional approach. The sampling technique used was purposive sampling with a total sample of 129 nurses. Collecting data using a questionnaire and analyzed using the Chi-Square test. The results of statistical tests showed that there was a significant relationship supervision (p=0.000) with electronic nursing documentation. The recommendation of this study is that hospital management is expected to be able to periodically supervise electronic nursing documentation, even in the current state of the Covid-19 pandemic.Keywords: Electronic Nursing Documentation, Nurse, Supervision